Erectile dysfunction predicts cardiovascular events in high-risk patients receiving telmisartan, ramipril, or both: The ONgoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial/Telmisartan Randomized AssessmeNt Study in ACE iNtolerant subjects with cardiovascular Disease (ONTARGET/TRANSCEND) Trials - Böhm, Michael; Baumhäkel, Magnus; Teo, Koon; Sleight, Peter; Probstfield, Jeffrey; Gao, Peggy; Mann, Johannes F; Diaz, Rafael; Dagenais, Gilles R; Jennings, Garry L R; Liu, Lisheng; Jansky, Petr; et al. (Circulation (New York, N.Y.), 2010)
Although erectile dysfunction (ED) is associated with cardiovascular risk factors and atherosclerosis, it is not known whether the presence of ED is predictive of future events in individuals with cardiovascular disease. We evaluated whether ED is predictive of mortality and cardiovascular outcomes, and because inhibition of the renin-angiotensin system in high-risk patients reduces cardiovascular events, we also tested the effects on ED of randomized treatments with telmisartan, ramipril, and the combination of the 2 drugs (ONTARGET), as well as with telmisartan or placebo in patients who were intolerant of angiotensin-converting enzyme inhibitors (TRANSCEND). In a prespecified substudy, 1549 patients underwent double-blind randomization, with 400 participants assigned to receive ramipril, 395 telmisartan, and 381 the combination thereof (ONTARGET), as well as 171 participants assigned to receive telmisartan and 202 placebo (TRANSCEND). ED was evaluated at baseline, at 2-year follow-up, and at the penultimate visit before closeout. ED was predictive of all-cause death (hazard ratio [HR] 1.84, 95% confidence interval [CI] 1.21 to 2.81, P=0.005) and the composite primary outcome (HR 1.42, 95% CI 1.04 to 1.94, P=0.029), which consisted of cardiovascular death (HR 1.93, 95% CI 1.13 to 3.29, P=0.016), myocardial infarction (HR 2.02, 95% CI 1.13 to 3.58, P=0.017), hospitalization for heart failure (HR 1.2, 95% CI 0.64 to 2.26, P=0.563), and stroke (HR 1.1, 95% CI 0.64 to 1.9, P=0.742). The study medications did not influence the course or development of ED. ED is a potent predictor of all-cause death and the composite of cardiovascular death, myocardial infarction, stroke, and heart failure in men with cardiovascular disease. Trial treatment did not significantly improve or worsen ED. URL: http://www.clinicaltrials.gov. Unique identifier: NCT 00153101.